Evaluation of the ankle position sense in the fatigue foot. Issue 3 (14th September 2018) - Yoshikawa, Masahiro; Nakasa, Tomoyuki; Sawa, Mikiya; Tsuyuguchi, Yusuke; Kanemitsu, Munekazu; Ota, Yuki; Adachi, Nobuo
Category: Ankle Introduction/Purpose: Previous studies have described the damage of sensori-motor control in ankle sprain as being a possible cause of functional instability. The methods to demonstrate the functional instability, have included the postural balance test, peroneal muscle reaction time to sudden ankle inversion, peroneal nerve conduction velocity, and joint position sense of the ankle. On the other hand, isokinetic fatigue of ankle plantar flexion and dorsiflexion exhibits the correlation with postural instability. We hypothesize muscle fatigue around ankle joint causes abnormality of joint position sense, especially inversion at ankle joint, and it will be one of the causes of the ankle sprain. The aim of this study was to evaluate the inversion angle replication errors of before fatigue and after fatigue. Methods: 11 subjects were included in this study. The subjects were placed in a sitting position with the knee flexed at 70°. Each subject placed the foot on a goniometer footplate with the ankle at 20° planter flexion. Subjects were blindfolded to eliminate visual input and to facilitate concentration during testing. The foot was passively rotated internally at random to one of six positions (5°to 30°), always starting from 0°. The footplate was rotated manually to the index angle in approximately 1 s, and held in position for 5 s. Then the ankle was returned to the 0° position. After that, the subjects moved their ankle to match the previous test angle actively. The difference between the index angle and replication angle was measured. Ankles were enforced planter and dorsiflexion according to previous reports, and replication error was measured before and after fatigue. Results: The side-to-side difference of the replication errors was 1.9±1.7° in the before-fatigue group and 2.6±1.8° in the after-fatigue group. There was a statistically significant difference between both the groups (p<0.05). In each inversion angle, there were significant differences of the side-to-side differences of the replication errors at 5°and 10°inversion angles (0.8±0.9°, 1.5±1.4° in the before-fatigue group and 2.2±1.7°, 2.6±1.5° in the after-fatigue group respectively). Conclusion: This study revealed the deficit of joint position sense in ankle inversion induced by fatigue. Fatigue may be one of the risk factor of ankle sprain through the deficit of joint position sense in inversion angle during sports activity.